2020
DOI: 10.1039/d0cc04339g
|View full text |Cite|
|
Sign up to set email alerts
|

Cage occupancy of methane clathrate hydrates in the ternary H2O–NH3–CH4 system

Abstract: The incorporation of ammonia inside methane clathrate hydrate is of great interest to the hydrate chemistry community. We investigated the phase behavior of methane clathrate formed from aqueous ammonia solution....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(35 citation statements)
references
References 30 publications
7
27
1
Order By: Relevance
“…2,12,13 The sII phase has a large to small cage ratio of 2 : 1 and in the case of partial occupancy of the small cages, this ratio becomes larger and can be consistent with values given in Fig. 2 of ref. 1.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…2,12,13 The sII phase has a large to small cage ratio of 2 : 1 and in the case of partial occupancy of the small cages, this ratio becomes larger and can be consistent with values given in Fig. 2 of ref. 1.…”
supporting
confidence: 89%
“…Recently Petuya et al published a study of the cage occupancies of methane in clathrate hydrates formed in the ternary H 2 O–NH 3 –CH 4 system, of particular interest for understanding the chemistry of Saturn's moon Titan. 1 In attempts to clarify the role of ammonia as a clathrate hydrate guest or a methane hydrate rate-enhancing agent and/or a hydrate inhibitor, the authors conclude that there was no direct evidence for the presence of ammonia in clathrate cages in the H 2 O–NH 3 –CH 4 system (above the eutectic at ∼200 K). The authors’ conclusion rests on observations of the phase behaviour, the interpretation of Raman spectra, and critiques of earlier work where evidence of enclathrated ammonia was presented.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A Comment 2 on this study argued against this interpretation: (1) it referred to works that interpreted the incorporation of ammonia in clathrate hydrates of methane and other species, formed not only by freezing of aqueous solutions but also other methods (cryogenic vapour deposition, aerosol condensation); (2) it challenged Petuya et al 1 and other previous publications that found no definitive evidence for a substantial incorporation of ammonia in methane clathrate hydrates formed from freezing of aqueous solutions; and (3) it examined the validity of the proposed mechanism of preferential destabilization of the large cages of the sI structure.…”
mentioning
confidence: 95%